Предмет: Алгебра,
автор: Shokoladka19952405
Упростите выражения
а)(sin x - cos x)^2/(sin2x-1)
б) 2sin a + (2cos^2 a)/(1+sin a)
Ответы
Автор ответа:
0
а)=(sin^2(x) - 2sinx*cosx+cos^2(x))(sin2x-1) = (1-sin2x)(sin2x-1) = -1
б)=(2sina+2sin^2(a)+2cos^2(a))(1+sina) = (2sina+2)(1+sina) = 2
б)=(2sina+2sin^2(a)+2cos^2(a))(1+sina) = (2sina+2)(1+sina) = 2
Похожие вопросы
Предмет: Математика,
автор: annaoniscenko
Предмет: Алгебра,
автор: soffka256
Предмет: Геометрия,
автор: igorm51
Предмет: Математика,
автор: irishamikheeva
Предмет: Математика,
автор: delgerj